Pelayanan Publik Bagi Bekas Warga Binaan di Balai Pemasyarakatan Kelas II Banda Aceh - Bestari, Putri; Muazzinah, Muazzinah; Khalil, Zakki Fuad (Journal of Public Administration and Local Governance, 2023)
In terms of public services within the Correctional Institution (Lapas) it certainly falls into the area of special public services involving certain publics. Even though it is special, it certainly does not reduce the quality of the public services that will be provided. Prisons as a training institution aim to make inmates into correctional facilities (WBP). The aim of this research is to determine public services for former inmates at the Banda Aceh Class II Correctional Center. This research method uses descriptive qualitative with data collection techniques through observation, interviews and documentation. Based on the results of research on all aspects of assessment based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 17 of 2017 concerning Guidelines for Performance Assessment of Public Service Providing Units with aspects of assessing service policies, professionalism of human resources, facilities and infrastructure, information systems, consultations and complaints, and public service innovations have been implemented well.